Dimensi Full day school dalam Budaya Masyarakat Pedesaan - Ahmad Munawir (Jurnal Commercium: Kajian Masyarakat Kontemporer, 2019)
The problem in this study is that full day school is applied in all schools in Indonesia, while in terms of school readiness, human resources, culture, and community characteristics differ between urban and rural areas. The purpose of this study is to describe the concept of full day school on aspects of school readiness, human resources, culture, and characteristics of communities in rural areas. The method used is qualitative research library type by recording all findings related to the concept of full day school. The results of the study explained that (a) the full day school system was not suitable for students in rural areas due to the unpreparedness of the school and inadequate human resources; (b) the concept of full day school is not in accordance with the characteristics and culture of rural communities due to the atmosphere that is still conducive, the role of parents who are still active in assisting their children, and the preservation of informal learning so that students can learn directly in the community.